Breast feeding practice and knowledge among mothers attending an urban Malaysian maternal and child health clinic - Radzniwan AR; Azimah NM; Zuhra H; Khairani O (Penerbit UKM, 2009)
The advantages of breastfeeding have been well established. The objective of this study was to determine the practice and knowledge of breastfeeding in an urban com-munity and identify the influencing factors. This is a cross-sectional study. All mothers attending the Maternal and Child Health Clinic during the study period, who fulfilled the selection criteria, were included in the study. The mothers were interviewed using a self administered questionnaire. A total of 162 mothers participated in the study. The prevalence of initiating breastfeeding during the first week after childbirth was 93.8%. Breastfeeding was found to be higher among Malay mothers (p value <0.001). Mother’s education level, employment status, husband’s occupation, family income and attending antenatal classes did not show significant association with breastfeeding practice. Influence from significant family members was found to be an important factor towards encouragement of breastfeeding. Overall, the mother’s knowledge on breastfeeding was fairly good. However, more than half (58.6%) did not know that they should continue breastfeeding even if the mother or the baby were sick. More than 20% of the mothers were still ignorant regarding ‘lactational amenorrhoea’, breast milk protection against allergy and that nipple soreness is common when breastfeeding. Approximately 15% of the mothers were not aware that breast milk is better than formula milk. In conclusion, although the mother’s knowledge on breast-feeding was fairly adequate, misconception in certain areas of breastfeeding needs correction.